Mongolia : Distributional Impact of Taxes and Transfers - Freije, Samuel; Yang, Judy (World Bank, Washington, DC, 2018)
This paper uses Mongolia's Household Socio Economic Survey for 2016 to estimate the distributive impact of taxes and transfers. The findings show that the system is progressive and contributes to reductions in poverty and inequality. The Gini coefficient of the pre-tax-and-transfer income is 0.4183 and decreases to 0.3507 after-tax-and-transfer. This is a reduction of 6.76 Gini points (around 16 percent). Something similar happens with the poverty rate, which decreases from 47.31 to 31.96 percent. Despite the progressiveness of the whole system, there are some caveats and policy warnings. First, pensions are the most redistributive instrument in the system, but their actuarial and fiscal sustainability is weak. Second, two programs (the child money program and the mortgage subsidy) do little redistribution -- the latter is actually regressive -- but represent a large share of the budget (around 2.5 percent of gross domestic product). These two factors, and the fact that up to a 35 percent of total expenditures in monetary and in-kind transfers is funded by corporate taxes and royalties -- which are highly dependent on volatile commodity prices—make the redistributive impact of the tax-and-transfer system susceptible to fiscal unsustainability.